2019
DOI: 10.1044/2018_jslhr-l-astm-18-0250
|View full text |Cite
|
Sign up to set email alerts
|

Linear Mixed-Model Analysis to Examine Longitudinal Trajectories in Vocabulary Depth and Breadth in Children Who Are Hard of Hearing

Abstract: Purpose Children who are hard of hearing (CHH) tend to have reduced vocabularies compared to children with normal hearing (CNH). Prior research on vocabulary skills in children with hearing loss has focused primarily on their breadth of knowledge (how many words are known). Depth of vocabulary knowledge (how well words are known) is not well documented for CHH. The current study used linear mixed models (LMMs) to investigate growth trajectories of vocabulary depth and breadth in CHH relative to age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 90 publications
1
31
0
2
Order By: Relevance
“…This may be of particular interest as new findings suggest that vocabulary depth may be hard to catch up at later ages (c.f. Walker et al, 2019). The findings from the current research are of clinical importance as delays in spoken vocabulary in children with CI have been reported in a number of studies (Geers et al, 2009; Fagan and Pisoni, 2010; Stiles et al, 2012; Coppens et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be of particular interest as new findings suggest that vocabulary depth may be hard to catch up at later ages (c.f. Walker et al, 2019). The findings from the current research are of clinical importance as delays in spoken vocabulary in children with CI have been reported in a number of studies (Geers et al, 2009; Fagan and Pisoni, 2010; Stiles et al, 2012; Coppens et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to the general cognitive and linguistic predictors of reading comprehension, children with CI have typically been found to perform more poorly than hearing peers on both decoding (Geers, 2003; Geers and Hayes, 2011; Nakeva von Mentzer et al, 2014), vocabulary (Geers et al, 2009; Fagan and Pisoni, 2010; Dillon et al, 2011; Coppens et al, 2013; Walker et al, 2019) and spoken language comprehension (e.g., Geers et al, 2009), as well as phonological and complex working memory (e.g., Wass et al, 2008). This would, in turn, suggest generally poorer preconditions for reading comprehension in this group of children.…”
Section: Introductionmentioning
confidence: 99%
“…The degree to which hearing loss limits speech audibility has been explored as a predictor of unaided (Scollie, 2008) and aided (Stiles et al, 2012; McCreery et al, 2015, 2017) speech recognition for children. In general, studies have found that children with hearing loss who have greater aided audibility for speech have better aided speech recognition in quiet (McCreery et al, 2015) and in noise (McCreery et al, 2017; Walker et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Mediation models (Baron and Kenny, 1986) have been used to examine the pattern of associations between outcomes and predictors that are inter-related. A recent study by Walker et al (2019) used a mediation analysis to determine if the effects of audibility on speech recognition for a gated word recognition task were direct or mediated by the relationship between audibility and language skills. The results suggested that audibility was related to both language and gated speech recognition, supporting both immediate, and cumulative influences of audibility.…”
Section: Introductionmentioning
confidence: 99%
“…Executive functions (EF) are connected to frontal lobe capacity (Kave et al, 2008) and represent underlying, interrelated processing skills, such as working memory, attention, and inhibition/flexibility, which all are important for several functions like communication, social cognition, and learning (Miyake et al, 2000;Diamond, 2013). Children with CI form a heterogeneous population with considerable variation, especially in EF (Figueras et al, 2008;Beer et al, 2014;Kronenberger et al, 2014) but also in the spoken language outcome (Boons et al, 2012;Löfkvist et al, 2012;Walker et al, 2019) and mental health (Hintermair, 2007;Anmyr et al, 2012;LingĂ„s-Haukedal et al, 2018). Poor EF in children with CI may negatively influence pragmatic skills, and especially in subgroups with known comorbid conditions like children with a cCMV infection.…”
Section: Introductionmentioning
confidence: 99%